Current trends of hybrid myocardial revascularization - Ya. A. Dyachenko; A. V. Gurshchenkov; G. I. Ishmukhametov; D. G. Zavarzina; V. S. Kucherenko; M. L. Gordeev (Вестник хирургии имени И.И. Грекова)
Despite the improvement of endovascular technologies, the method of choice for multi-vascular lesions of the coronary arteries today remains coronary bypass surgery. However, in a range of patients, it is possible to perform hybrid revascularization – a technique with minimal injury that preserves good long-term results similar to those of coronary bypass surgery. The review analyzes current data from the world literature and current trends in the choice of the revascularization method.